The impostor phenomenon in the eye of knowledgeable others: the association of the impostor phenomenon with the judge’s accuracy - Ibrahim, Fabio; Brill, Erik; Meyberg, Tobias; Herzberg, Philipp Yorck (Frontiers in Psychology, 2023)
This study examines whether a heightened impostor expression is associated with a judge's assessment.The sample comprised n = 155 triads (target, mother, and a friend). Results indicated a slightly higher profile agreement between the target and mother (rraw = .47; rdistinct = .33) than a friend (rraw = .41; rdistinct = .23). The profile agreement was inversely correlated with the IPP total score, Competence Doubt, Alienation, and Other-Self Divergence (r = ≤-.29, p < .001), indicating reduced accuracy among judges when confronted with a heightened impostor expression. However, these relationships disappear once controlling for stereotype effects. Overall, this study reveals a negative association between the impostor expression and the other-self agreement, supporting the biasing self-presentation of impostors in the eye of others.